Implementation of the Al-Qur'an Disferentiation Learning Model in Metavers Era Children - Nakhma'Ussolikhah; Moh Iqbal Al Ghazali; Lina Marliana (International Journal of Education and Humanities, 2023)
The golden age is a golden period for children to develop optimally. The problem that occurs in early childhood is the wrong way of teaching, such as applying conventional learning methods without teaching aids and without media, children become bored and fed up. mentally. The purpose of this research is to improve the Al-Qur'an learning model for early childhood with the help of media. The methodology used is a qualitative approach with a case study design. This research was conducted at the Al – Biruni Cirebon foundation. The main respondents in this study were 3 students aged 5-6 years and 2 accompanying teachers and the secondary subjects were the students' parents. The data collection instrument used was interviews. The results of the research provide an illustration that young children can understand the concept of learning through audio-visual media with pleasure and joy. Teachers and parents collaborate to help the Islamic learning process. Habits at school can be implemented at home so that children do not forget easily and there is a method of parents or teachers continuously accompanying children at school. Learning the Al-Qur'an can help increase student interest and make it easier for students to memorize verses of the Al-Qur'an. Maintain and memorize generously